Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Pesisir Selatan - Deri Farma; Desi Permata Sari; Shinta Bella (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to determine and try to analyze the Influence of Leadership Style and Work Environment on Employee Performance with Job Satisfaction as an Intervening Variable at the Education and Culture Office of Pesisir Selatan Regency. This study is a Structural Equation Modeling (SEM) model with SmartPLS 3.0 analysis tools. The population and sample of this study are employees of the Education and Culture Office of Pesisir Selatan Regency. The research results found a positive and significant effect between leadership style and job satisfaction. There was a positive and significant effect between the work environment and job satisfaction. There was a positive and significant effect between leadership style and employee performance. There was a positive and insignificant effect between the work environment and employee performance. There was a positive and significant effect between job satisfaction and employee performance. Job satisfaction mediated the relationship between leadership style and employee performance. Job satisfaction mediated the relationship between the work environment and employee performance.